Prolonged Activation of Invariant Natural Killer T Cells and TH2-Skewed Immunity in Stroke Patients - Wong, Connie H. Y.; Jenne, Craig N.; Tam, Patrick P.; Léger, Caroline; Venegas, Andres; Ryckborst, Karla; Hill, Michael D.; Kubes, Paul (Frontiers in Neurology, 2017)
Background: Infection is highly prevalent and contribute significantly to mortality of stroke patients. In addition to the well described robust systemic lymphocytopenia and skewed T helper 2 (TH2)-immunity after stroke, emerging experimental evidence demonstrate that the development of infection post-stroke is attributed by the activation of invariant natural killer T (iNKT) cells. In this prospective study, we examined the levels of a broad spectrum of inflammatory mediators, the activation status of iNKT cell in the blood of patients with various degree of stroke severity, and investigate whether these parameters differ in patients who later develop post-stroke infections. Methods and Results: We obtained blood from stroke patients and matching controls to perform flow cytometry and multiplex measurement of inflammatory mediators. Our data suggest a pronounced activation of iNKT cells in stroke patients as compared with matched healthy and hospital control patients. The magnitude of iNKT activation is positively correlated with the severity of stroke, supporting the hypothesis that iNKT cells may contribute in the modulation of the host immune response after stroke-associated brain injury. In addition, stroke severity is closely correlated with decreased TH1/TH2 ratio, increased production of interleukin- (IL-) 10, with infected stroke patients showing exacerbated production of IL-10. Conclusions: Stroke triggers a robust and sustained shift in systemic immunity in patients, including specific lymphopenia, robust activation of iNKT cells, systemic production of IL-10, and a prolonged TH2-skewed immunity, all are potential contributors to severe immune suppression seen in patients after stroke. Future studies with large sample size will provide potential causality relationship insights.